Application of business intelligence for analyzing vulnerabilities to increase the security level in an academic CSIRT - Reyes Mena, Francisco Xavier; Fuertes Díaz, Walter Marcelo; Guzmán Jaramillo, Carlos Enrique; Pérez Estévez, Ernesto; Bernal Barzallo, Paúl Fernando; Villacís Silva, César Javier (Universidad Pedagógica y Tecnológica de Colombia, 2018)
1 recurso en línea (páginas 21-29).